1996
DOI: 10.1212/wnl.46.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Trinucleotide repeat length and clinical progression in Huntington's disease

Abstract: We examined the relationship between length of the trinucleotide (CAG) repeat at IT-15 and clinical progression of Huntington's disease in 46 mildly to moderately affected patients over a 2-year interval. Patients were divided into those with short mutations (37 to 46 repeats; n = 25) and those with long mutations (> or = 47 repeats; n = 21). Patients with long repeat lengths had earlier age at onset and were younger and less functionally impaired than those with short repeats at the initial visit, but the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 22 publications
5
87
0
1
Order By: Relevance
“…Analysis of the CAG repeat region among 44 HD patients (39-66 CAGs) and 51 normal individuals (9-34 CAGs) showed that the range of the repeat size was similar to previous reports in other populations (Andrew et al, 1993;Huntington's Disease Collaborative Research Group, 1993;Andrew and Hayden, 1995;Brandt et al, 1996;Pramanik et al, 2000). In addition, the mean CAG size of 102 normal chromosomes of Croatian origin (18.5 ± 3.5) was found to resemble that for a Western European populations (18.4 ± 3.7) and was considerably higher than the mean CAG lengths found on Black, Chinese, Japanese and Finnish normal chromosomes (16.5 ± 1.7) (Squitieri et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Analysis of the CAG repeat region among 44 HD patients (39-66 CAGs) and 51 normal individuals (9-34 CAGs) showed that the range of the repeat size was similar to previous reports in other populations (Andrew et al, 1993;Huntington's Disease Collaborative Research Group, 1993;Andrew and Hayden, 1995;Brandt et al, 1996;Pramanik et al, 2000). In addition, the mean CAG size of 102 normal chromosomes of Croatian origin (18.5 ± 3.5) was found to resemble that for a Western European populations (18.4 ± 3.7) and was considerably higher than the mean CAG lengths found on Black, Chinese, Japanese and Finnish normal chromosomes (16.5 ± 1.7) (Squitieri et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
“…HD alleles have 36 CAGs in the HD gene (also called IT15), while normal individuals have between 10-35 CAG units (Huntington's Disease Collaborative Research Group, 1993). The severity and age at onset of HD inversely correlates with CAG repeat length; longer repeats cause an earlier age of onset (Andrew et al, 1993;Brandt et al, 1996;Brinkman et al, 1997). HD is characterized by uncontrolled movements (chorea), accompanied with cognitive and/or psychiatric distrurbances (Andrew et al, 1993;Cummings, 1993;Brandt et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PPAR␥ activation by rosiglitazone up-regulates the Bcl-2 protective pathway and prevents neuronal degeneration induced by both oxidative stress and treatment with A␤ fibrils, with a concomitant increase in mitochondrial viability (22). Recent studies have also provided evidence that the expression of PGC-1␣, a potent co-activator of PPAR␥, is repressed by mutant huntingtin expression, and when PGC-1␣ knock-out (KO) mice are crossed with HD knockin mice, this resulted in increased neurodegeneration of striatal neurons and motor abnormalities in the HD mice (2). At the same time, there is evidence suggesting that PPAR␥ agonists are neuroprotective and increase mitochondrial function (23,24).…”
mentioning
confidence: 99%
“…3 The probability that the gene is inheritable transimissible is 50%. 4,5 We present the case of a person with Major Neurocognitive Disorder and Huntington's Disease with a rapid progression in the neuropsychological domains.…”
Section: Introductionmentioning
confidence: 99%